Floral nectaries of Heliocarpus popayanensis and Luehea divaricata (Malvaceae-Grewioideae): Structure and ultrastructure - Lattar, Elsa Clorinda (2018)
The structure and ultrastructure on floral nectaries of Heliocarpus popayanensis Kunth. and Luehea divaricata Mart (Malvaceae-Grewioideae) were investigated for the first time. The floral nectaries of the analysed species are structured (can be recognised macroscopically and microscopically) and of trichomatic type. Significant morphological differences were observed between the nectaries of perfect and pistillate flowers of H. popayanensis, as well as between nectaries of this species and those of the related species, Triumfetta rhomboidea Jacq. The volume of nectar produced in the perfect and pistillate flowers of H. popayanensis and in the perfect flowers of L. divaricata presents significant differences that could be related to the rewards offered to flower visitors. No differences were observed in ultrastructure features of the glandular trichomes between H. popayanensis and L. divaricata. Nectar accumulation occurs between the wall and the cuticle. The predominant floral visitors in perfect and pistillate flowers of H. popayanensis were bees, and less frequently flies; whereas for L. divaricata were wasps, bumblebees, butterflies and beetles. Our results support the inclusion of each genus in different tribes according to the recent tribal classification based on molecular and morphological data of the subfamily Grewioideae.